CONTACT BRACHYTHERAPY IN THE TREATMENT OF SUPERFICIAL NON-MELANOMA SKIN CANCER: SINGLE INSTITUTIONAL EXPERIENCE - Klisarovska, Violeta; Trpkovska, Biljana (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Introduction: Contact brachytherapy allows satisfactory treatment of superficial non-melanoma skin cancer, whether as adjuvant and/or definitive therapy. There are different techniques and different dose prescriptions in clinical practice, adapted to technical possibilities.  Material and methods: 50 patients treated with contact brachytherapy for superficial non-melanoma skin cancer were analyzed, 15 of them in a postoperative and 35 in a definitive setting. Histopathologically, 40 patients had verified basal cell carcinoma and 10 had squamous cell carcinoma. High dose rate brachytherapy was performed with the GammaMed Plus tm , with a radioactive Iridium192. A Leipzig-style cone contact applicator set with a diameter range of 10-45 mm was used. In 40 patients, a hypofractionated regimen was performed, with one fraction per week, with a dose of 7Gy, a total of 4 fractions, to achieve a total dose of 28Gy, over 4 weeks. A dose of 30Gy with a single fraction of 5Gy, over 6 weeks was administered to 10 patients, respectively, regardless of histological type. The dose was prescribed to a depth of 5 mm of the skin.  Results: Local control was confirmed in 47 patients. In 3 patients the disease recurred 10 months after the last treatment (7Gy/4fr/28Gy). Skin redness was manifested in all patients (100%). Telangiectasia presented at the end of the treatment in 4 patients. At the first visit, all patients had reduced or completely disappeared inflammatory reactions.  Conclusion: Our experience with the use of hypofractionated regimens has shown that it is a safe treatment, with easily manageable side effects. Key words: brachytherapy, hypofractionating, skin cancer.